TECHNOLOGICAL MINERALOGY OF IRON ORE RIEBECKITE METASOMATITES OF KRYVYI RIH BASIN - Streltsov, V.; Evtekhov, V.; Evtekhova, A.; Shepelyuk, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Riebeckite metasomatites belong to the widespread varieties of low-grade magnetite ores of Pervomaiske, Hannivske, Petrivske, Artemivske and some other deposits of Kryvyi Rih basin. Riebeckitization of magnetite quartzites was accompanied by changes in the size, shape of crystals and aggregates of magnetite and nonmetallic minerals, their contact nature, and the quantitative relationships of ore-forming and secondary minerals. Thus, metasomatosis has caused changes in mineralogical indexes of ores, which have a decisive influence on ore preparation characteristics. The main index of metasomatism intensity is the average Na2O content in the primary magnetite quartzites which is close to 0; in the zones of weak metasomatic changes represented by riebeckitized magnetite quartzites, its value increases up to 0.58 mass.%; in zones of moderate metasomatic changes (riebeckite-magnetite quartzites) it is up to 1.49 mass.%; in the zones of the most intensive metasomatic transformations, composed of magnetite-riebeckite metasomatites (riebeckitites) it is up to 2.34 mass.%. The increase in metasomatism intensity has caused a noticeable increase in the total iron content in magnetite-riebeckite metasomatites compared with the initial magnetite quartzites due to the partial removal of silica by alkaline solutions. The iron content, which is a part of magnetite, decreases in the same way due to the partial substitution of magnetite by riebeckite. The main technological parameter, which determines the efficiency of ore processing, is the total iron content in the concentrate produced. The value of this index gradually and regularly grows from unaltered magnetite quartzites to riebeckitites. The reason is that an increase in riebecktization activity contributed to the approximation of magnetite individual forms to crystallographically perfect ones. The consequence of this is the improvement in magnetite crystals and aggregates release when grinding ores, the reduction in nonmetallic minerals entrainment in the concentrate in aggregates composition. Negative consequence of riebeckitization consists in deterioration of the three other technological indexes of low-grade magnetite ores. They are: concentrate yield, iron extraction, and iron content in concentration waste (tailings). The reduction in the concentrate yield is associated with a decrease of magnetite content in ores due to its partial replacement with riebeckite. The decrease in the index of the iron recovery into the concentrate is due to the same fact: it receives iron from magnetite, while riebeckite iron is removed to the concentration waste. This explains the significant increase (from 8.04 to 20.79 mass.%) of the total iron content in tailings. Thus, the riebeckitization of magnetite quartzites is characterized by a contrariety in terms of the mineralogical-technological relation. On the one hand, it was accompanied by the increase in concentrate quality, on the other hand by a decrease in concentrate yield and iron recovery into concentrate. The iron content of the concentrate being the main indicator for technological process efficiency, in general, riebeckitization can be considered to be a process that contributed to improving the processing of low-grade magnetite ores.
Keywords: banded iron formation; Kryvyi Rih basin; magnetite ores; sodium metasomatism; mineral composition; chemical composition; ore preparation characteristics